Efficacy and cerebral mechanism of acupuncture and moxibustion for treating primary dysmenorrhea: study protocol for a randomized controlled clinical trial - Xiaohui Dong; Jie Yang; Wei Wei; Ling Chen; Menghua Su; Aijia Li; Xiaoli Guo; Liying Liu; Shenghong Li; Siyi Yu; Fang Zeng (Trials, 2022)
Abstract Background Acupuncture or moxibustion has been proven to be effective for patients with primary dysmenorrhea (PDM). However, the respective advantages and potential central mechanism of acupuncture and moxibustion are worthy of investigating to promote their further application. Methods In this randomized controlled neuroimaging trial, 72 patients with PDM will be randomly assigned to three groups: acupuncture treatment group, moxibustion treatment group, and waiting list group. The acupuncture treatment group and moxibustion treatment group will receive acupuncture or moxibustion, respectively, for a total of 3 sessions over 3 consecutive menstrual cycles, and the waiting list group will not take acupuncture or moxibustion during these 3 menstrual cycles. The COX Menstrual Symptom Scale (CMSS), visual analog scale (VAS), and Pain Catastrophizing Scale (PCS) will be used to evaluate the clinical efficacy. The Self-rating Depression Scale (SDS), Self-rating Anxiety Scale (SAS), and 36-Item Short Form Health Survey (SF-36) will be used to assess the mental state and quality of life at baseline and at the end of treatment. Functional magnetic resonance imaging (fMRI) will be performed for detecting the cerebral activity changes at baseline and at the end of the treatment. The clinical data and imaging data will be analyzed among the groups. Correlation analysis will be conducted to investigate the relationship between brain functional changes and symptom improvement. Discussion The application of the randomized controlled neuroimaging trial will provide objective and valid evidence about how acupuncture and moxibustion treatment relieve menstrual pain. The results of this study would be useful to confirm the potential similarities and differences between acupuncture and moxibustion in clinical efficacy and central mechanism for patients with PDM. Trial registration Chinese Clinical Trial Registry ChiCTR2100043732 . Registered on 27 February 2021